2017
DOI: 10.3389/fpsyg.2017.01172
|View full text |Cite
|
Sign up to set email alerts
|

Combining Standard Conventional Measures and Ecological Momentary Assessment of Depression, Anxiety and Coping Using Smartphone Application in Minor Stroke Population: A Longitudinal Study Protocol

Abstract: Context: Stroke has several consequences on survivors’ daily life even for those who experience short-lasting neurological symptoms with no functional disability. Depression and anxiety are common psychological disorders occurring after a stroke. They affect long-term outcomes and quality of life but they are difficult to diagnose because of the neurobiological consequences of brain lesions. Current research priority is given to the improvement of the detection and prevention of those post-stroke psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
(119 reference statements)
0
7
1
Order By: Relevance
“…Many studies indicated the persistence and mutuality of post-stroke anxiety (Cumming et al, 2016). Through our investigation, the frequency of anxiety (51.7%) was not consistent with other studies that demonstrated lower frequency after 3 months of stroke, with an estimated prevalence ranging between 18 and 38% (Barker-Collo, 2007;Ayerbe et al, 2014;Vansimaeys et al, 2017). The high level of anxiety in Lebanon could be related to the lack of rehabilitative services following stroke, the lack of social and psychological support for the survivor, and the high burden of physical disability on them.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Many studies indicated the persistence and mutuality of post-stroke anxiety (Cumming et al, 2016). Through our investigation, the frequency of anxiety (51.7%) was not consistent with other studies that demonstrated lower frequency after 3 months of stroke, with an estimated prevalence ranging between 18 and 38% (Barker-Collo, 2007;Ayerbe et al, 2014;Vansimaeys et al, 2017). The high level of anxiety in Lebanon could be related to the lack of rehabilitative services following stroke, the lack of social and psychological support for the survivor, and the high burden of physical disability on them.…”
Section: Discussioncontrasting
confidence: 84%
“…Classically, a score of eight or more for each subscale is used as a cut-off score in studies to distinguish between cases of depression and anxiety and the unharmed. This cut-off point is also frequently used in the population of stroke and has adequate specificity and sensitivity in recognition of depression and anxiety disorders after stroke (Vansimaeys et al, 2017 ). The Arabic validated version of HADS was used in our study (Al Aseri et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We coded studies reporting unrestricted data collection as number of measures and coded studies reporting restricted data collection as number of modules . A range of studies measured the number of outcome surveys completed from those assigned [45,68,75]. Others assessed the number of videos watched from a playlist [36,55], educational modules completed [52], or self-care advice accessed [69].…”
Section: Resultsmentioning
confidence: 99%
“…To date, seven studies used EMA across acute to chronic stroke survivors to study post-stroke depressive symptoms, 16,[33][34][35][36][37][38] two other studies report about fatigue, 39,40 and one focuses on the interaction between social interactions, pain, fatigue, and mood. 41 EMA provides insights on the fluctuation of mood in daily life, 34,42,43 the behavioral risk factors for depression, 16,35,36 and the impact of early social contact and support on longterm depression and daily life functioning. 33 EMA was also used in combination with magnetic resonance imaging (MRI) to characterize the association between depressive symptoms in daily life and cerebellar volume.…”
Section: Ecological Momentary Assessment Has Been Used For Stroke Surmentioning
confidence: 99%